2014
DOI: 10.1161/hypertensionaha.113.02313
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Eukaryotic Initiation Factor 2α Kinase General Control Nonderepressible 2 Protects Mice From Pressure Overload–Induced Congestive Heart Failure Without Affecting Ventricular Hypertrophy

Abstract: In response to a number of stresses, including nutrient deprivation, General Control Nonderepressible 2 kinase (GCN2) attenuates mRNA translation by phosphorylating eukaryotic initiation factor 2 alpha (eIF2αSer51). Energy starvation is known to exacerbate congestive heart failure (CHF) and eIF2αSer51 phosphorylation is increased in the failing heart. However, the impact of GCN2 during the evolution of CHF has not been tested. In this study we examined the influence of GCN2 expression in response to a cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…Deletion of the PKR gene (KO) markedly attenuated Transverse Aortic Constriction (TAC)-induced CHF in mice 2 . In addition, we demonstrated that genetic disruption of the eIF2α protein kinase GCN2 also significantly attenuated TAC-induced CHF in mice 3 . However, the effect of eIF2α protein kinase PERK on TAC-induced CHF is unknown.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Deletion of the PKR gene (KO) markedly attenuated Transverse Aortic Constriction (TAC)-induced CHF in mice 2 . In addition, we demonstrated that genetic disruption of the eIF2α protein kinase GCN2 also significantly attenuated TAC-induced CHF in mice 3 . However, the effect of eIF2α protein kinase PERK on TAC-induced CHF is unknown.…”
Section: Introductionmentioning
confidence: 80%
“…We previously reported that LV dysfunction causes severe lung fibrosis and lung vascular remodeling 3, 16 , which is anticipated to exacerbate the progression of CHF. Therefore, we examined TAC-induced lung fibrosis and lung vascular remodeling in wild type and PERK KO mice (Figure S10A-D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonatal rat cardiomyocytes were collected and plated in 10% FCS/DMEM as described previously (Lu et al, 2014). After 24 h of serum starvation, Ang II (1 μM) in the presence or absence of different concentrations of TAX (0 μM, 5 μM, 10 μM, 25 μM, 50 μM) was added to the medium.…”
Section: Methodsmentioning
confidence: 99%